2008
DOI: 10.1063/1.2964093
|View full text |Cite
|
Sign up to set email alerts
|

Strong terahertz conductance of graphene nanoribbons under a magnetic field

Abstract: We demonstrate that the optical response of graphene nanoribbons in the terahertz to far-infrared regime can be significantly enhanced and tuned by an applied magnetic field. The dependence of the threshold frequency on the magnetic field is studied. The ribbons with the strongest terahertz conductance under a magnetic field are those with one-dimensional massless Dirac Fermion energy dispersion. For a given ribbon, there exists an optimal field under which the conductance resonance can occur at the lowest fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
70
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(71 citation statements)
references
References 34 publications
1
70
0
Order By: Relevance
“…Second, and most important, the transition between the highest valence and lowest conduction bands become optically active owing to the acquired dispersion next to the boundaries (figure 3b). This effect is known as magnetic enhancement of the THz conductance (Liu et al 2008b). However, it does not extend much into the visible range, keeping the nanoribbons mostly transparent.…”
Section: (B) Transverse Magnetic Fieldmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, and most important, the transition between the highest valence and lowest conduction bands become optically active owing to the acquired dispersion next to the boundaries (figure 3b). This effect is known as magnetic enhancement of the THz conductance (Liu et al 2008b). However, it does not extend much into the visible range, keeping the nanoribbons mostly transparent.…”
Section: (B) Transverse Magnetic Fieldmentioning
confidence: 99%
“…When the nanoribbon is illuminated by a linearly polarized light along the ribbon, the optical conductance can be calculated via the Kubo formula (Johnson & Dresselhaus 1973;Liu et al 2008b). For the purpose of studying the symmetry breaking in external fields, the optical field can be represented as two circularly polarized waves, yielding the optical conductance in the following form:…”
Section: Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The optical conductivity of SLG and bilayer graphene has been calculated [15][16][17][18], as has the conductance of various GNRs [19]. All of this research has shown that the optical response of graphene and graphene nanoribbon is extremely weak.…”
mentioning
confidence: 99%
“…1,2 For example, the prediction and observation of electron-hole symmetry and a half-integer quantum Hall effect, [3][4][5] finite conductivity at zero chargecarrier concentration, 3 the strong suppression of weak localization, [6][7][8] universal conductance, 9-11 magnetic enhancement of optical conductance in graphene nanoribbons, 12 and strong nonlinear response in the terahertz frequency regime. 13,14 Additional unique properties can be found in bilayer graphene ͑BLG͒.…”
Section: Zr Froru Whudkhuw] Uhvsrqvh Lq Elod\hu Judskhqh Qdqruleerqvmentioning
confidence: 99%